DETEKSI BUKTI DIGITAL ONLINE GAMBLING MENGGUNAKAN LIVE FORENSIK PADA SMARTPHONE BERBASIS ANDROID - Andrian Sah; Imam Riadi; Yudi Prayudi (Cyber Security dan Forensik Digital, 2018)
Internet as media to do political movement. Since that, the Indonesian people understand internet-based activities until this current progress. Use of internet in Indonesia most frequently utilize units to access internet, namely, handphone, laptop/notebook, Personal Computer (PC), and tablet. Media used to access internet include mobile (47.6%), computer (1.7%) and both (50.7%). Use of internet increases so that criminal action rate is higher; for example, online gambling. In general, online gambling is done using smartphone. However, today smartphone can load more than one type of online gambling. So speedy progress of online gambling  must contain criminal action. Criminal action is taken by involving smartphone having online gambling with impact on challenge to prove digital evidences and analyze it. Online gambling is a crime or criminal action  being social problems resulting in negative impacts such as morale and mental disorders in society, especially young generation. Questions asked in this study are how to find characteristic of online gambling and digital evidences available to smartphone. This study focuses on characteristic and digital evidences in smartphone based on facts found in thing of evidence. Based on results of study, we found some types of online gambling in smartphone. Characteristic and digital evidences found in smartphone were found by using forensic media, namely, XRY. Forensic media of XRY were used to find thing of digital evidence in smartphone, such as, ID, Password and transaction of online gambling via social applications.